The Use of Infra Red Aerial Photo for Identification the Existance and Spread of Cave in Planning sub District, Eromoko District, Wonogiri Regency - S Suharjo; Sugiharto Budi Santoso; Reshinta Purnaningsih; S Suryanto; Yuliarta Rudi Prasetyo (Forum Geografi, 2001)
Science that studied all of the aspect related to cave and their circles (speleology) in Indonesia does not still quite expand. Expantion more advanced need all sorts of research, publication and its interest to an academic party who get in touch with cave and their circles. One of them the basic of data collection about the existence and the spread of cave. The usual manner that is used to know the existence and the spread of cave, is by means of the analysis topography map which is continued by terrestrial research. Weakness for this manner is it need huge time, cost and energy. The making use of aerial photo can be done in supporting the basic of date collection, is the· interpretation to bug or detect appearances the phenomena in earth’s surface. One of them is appearances the edge of cave. The result of the research indicates that interpretation of aerial photo can be use to identify the spread of the edge of cave. It is olksified according to; the edge that obtained of center depression by the accuracy of 100%; the edge of cave that obtained of slope depression (the accuracy of 33.3%); the edge of cave that is obtained of river current (the accuracy of 100%); and the edge of cave that obtained of fragment (the accuracy of 50%).